Decreased ratio of influenza-specific IgG versus IgM in response to influenza vaccination in antiretroviral-treated HIV-infected African Americans compared to Caucasians, and its direct correlation with the percentages of peripheral Tfh cells - Ma, Ping; Luo, Zhenwu; Qian, Jing; Yan, Zhongfang; Zhang, Lumin; Martin, Lisa; Wang, Ziyu; Xia, Huan; Yu, Fangfang; Jiang, Wei (Vaccine, 2020)
Racial differences have been observed in the rate of bacterial infection and disease progression in HIV. Here, we evaluate racial differences in seasonal influenza vaccine responses. 16 healthy controls (9 Caucasians (CC) and 7 African Americans (AA)) and 26 antiretroviral therapy (ART)-treated aviremic HIV+ subjects (11 CC and 15 AA) were enrolled in the current study. Blood was collected at pre-vaccination (D0) and day 14 (D14) following seasonal influenza vaccination. Serologic responses were characterized in plasma by ELISA. B and T cells were assessed by flow cytometry ex vivo. The absolute counts of CD4+ CD3+ T cells and CD19+ B cells were similar in healthy controls and HIV-infected individuals, and similar in CC and AA in the two study groups. However, the percentage of peripheral T follicular helper (pTfh) cells was decreased in HIV+ AA compared to HIV+ CC. There were no racial differences in IgG antibody responses against vaccination in the two study groups. However, the ratio of anti-influenza-specific IgG versus IgM induction following vaccination was decreased in HIV+ AA compared to HIV+ CC, which was directly correlated with the percentages of pTfh cells. This racial difference and correlation were not demonstrable in healthy controls. Here we report that HIV + AA has decreased fold induction of IgG versus IgM after influenza vaccination, which may suggest impaired class-switching from IgM to IgG in AA HIV-infected individuals.